Sistem Informasi Koordinat Prakiraan Daerah Penangkapan Ikan Tuna Bagi Nelayan - Sugiari Sugiari (Jurnal Jaringan Telekomunikasi, 2015)
One of the products of Indonesia's fishery is Tuna. To overcome the increasing demand of the world market, the Ministry of Marine Affairs and Fisheries provides routine information on map information on potential zones of fish, especially Tuna. However, for some fishermen it is relatively difficult to access the map because it requires the internet, so it becomes an obstacle in disseminating information on this fish potential zone map. From the above problems, such as the lack of knowledge of fishermen regarding the condition of the location of tuna points, while the current information is relatively difficult to obtain for some fishermen, so it is necessary to develop a "Coordinating Information System for Tuna Fish Estimates for Fishermen". With this system, it can make it easier for fishermen to subscribe to tuna fish coordinate update information either through the website or via SMS. The method used to determine the coordinates of the fish on the PDPI map is to use image processing with the medium scaling method SMS was chosen because it is one of the media for transferring information that is widely used among middle to lower income fishermen. From the results of testing and analysis of software. digital coordinates can run with an average reading duration of 31.651 seconds. The map error tolerance for longitude is 1099,591 meters and for latitude is 1401,939 meters.